Cotton pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'Cotton Insect Pests and Their Management' by G A Matthews, 1989, 199pp, ISBN 0 582 00561 2, price UKL 17.95